Komposisi Dan Struktur Komunitas Fitoplankton Di Perairan Teluk Sungai Pisang Kota Padang Sumatera Barat pada Musim Kemarau - Indra Junaidi Zakaria; Chairul Chairul; Ahmad Mursyid; Gusna Merina (Jurnal Laot Ilmu Kelautan, 2023)
AbstractSungai Pisang Bay is located south of Padang City, at this location there are various activities including Pasumpahan Island water tourism, fishing, and settlement activities. This is expected to pollute the sea and have an impact on marine biota, especially phytoplankton. The purpose of this study was to examine the quality of seawater based on the composition and structure of the phytoplankton community in the Sungai Pisang Bay, Padang City. The research was conducted using survey methods and field sampling using plankton net at three sample stations on Pasumpahan Island, Ujung and Setan Island. The result is conducted 100 species of phytoplankton were found consisting of 4 classes, namely Bacillariphyceae 66 species, Chlorophycaeae 1 species, Cyanophyceae 3 species and Dinophyceae 30 species. The phytoplankton diversity index in April ranged from 2.056-3.165 and in Mei 2.644-2.977. The phytoplankton equitability index in April ranged from 0.565-0.836 and in Mei 0.727-0.809. The phytoplankton dominance index in April ranged from 0.054-0.087 and in Mei 0.096-0.131. Physical Chemistry in good condition base on KEPMEN LH No 51/2004. It can be concluded that the condition of Sungai Pisang Bay waters is based on the presence of phytoplankton in dry conditions is good.